Learning to Lament: Complaining to God about the Decline of the Church - Carswell, John (The expository times, 2020)
In this paper I want to consider using the book of Lamentations as a metaphor for understanding the suffering occasioned by the decline of the Western church, specifically the drastic fall in church membership and participation witnessed in Britain from the mid-twentieth century to the present. It is my contention that the church needs a way in which to speak its own hurt and disappointment with God, its heart-cry and its complaint, and that Lamentations provides a theological framework in which it might parse the various elements of its grief with the aim of understanding church decline within the providence of God. Lament gives the church the permission and the language to blame God for its decline, and to seek God as its singular hope for a future.